Pengaruh Profitabilitas, Likuiditas, dan Struktur Modal Terhadap Financial Distress pada Perusahaan Manufaktur yang Terdaftar di BEI 2019-2021 - Yoga Agung Indrawan (Universitas Sains dan Teknologi Komputer, 2023)
This study aims to determine and analyze the effect of profitability, liquidity, and capital structure on financial distress. This study uses a sampling technique that is purposive sampling. The population used in this study are manufacturing companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The analytical method used is SPSS. The results of this study prove that profitability has a negative and significant effect on financial distress, liquidity has a negative and significant effect on financial distress, but capital structure has no effect on financial distress